Penerapan model pembelajaran Quantum Teaching untuk meningkatkan keterampilan bereksperimen dalam pembelajaran IPA - Wahidurahman, Nazza; Kartono, Kartono; Hadiyah, Hadiyah (JPI (Jurnal Pendidikan Indonesia): Jurnal Ilmiah Pendidikan, 2019)
The purpose of this research is to improve third grade students’ experimental skills byapplication Quantum Teaching learning model. Form of this research is classroomaction that lasts two cycles. The subject of this research war teacher and third gradestudents’ of Elementary School Purwotomo 97 Surakarta in 2017/2018 academic yearamounted to 18 students. Data collection techniques are conducted by interview,observation, and document analysis. Data validity techniques is content validity andtechnical triangulation. Data analysis technique is a quantitative descriptive techniqueand interactive analysis. Conclusion of this research is applicating of the QuantumTeaching learning model can improve student experiment skills.